Ostracism and the provision of a public good - Frank P. Maier-Rigaud; Peter Martinsson; Gianandrea Staffiero (Max Planck Institute for Research on Collective Goods, 2005)
We analyze the effects of ostracism on cooperation in a linear public good experiment. Our results show that introducing ostracism increases contributions. Despite reductions in group size due to ostracism, the net effect on earnings is positive and significant.
Keywords: C92; H41; 330; Experiment; Public Good; Ostracism